2021
DOI: 10.1111/2041-210x.13685
|View full text |Cite
|
Sign up to set email alerts
|

Building ecological networks with local ecological knowledge in hyper‐diverse and logistically challenging ecosystems

Abstract: 1. Collecting interaction data to build frugivory or seed dispersal networks is logistically challenging in ecosystems that have very high plant and animal diversity and/ or where fieldwork is difficult or dangerous. Consequently, the majority of available networks are from ecosystems with low species diversity or they represent a subset of the community.2. Here, we propose an approach applying local ecological knowledge (LEK) of indigenous communities to build quantitative interaction databases and networks t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 51 publications
0
26
1
Order By: Relevance
“…Our study identified the importance of the different seed dispersers in an almost intact community in a Sundaic rainforest using unconventional methods (Ong, Campos-Arceiz, Loke, et al, 2021), and is one of the first community-wide seed dispersal studies in this mega-diverse region (Kitamura et al, 2002). Nonetheless, there were several caveats.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Our study identified the importance of the different seed dispersers in an almost intact community in a Sundaic rainforest using unconventional methods (Ong, Campos-Arceiz, Loke, et al, 2021), and is one of the first community-wide seed dispersal studies in this mega-diverse region (Kitamura et al, 2002). Nonetheless, there were several caveats.…”
Section: Discussionmentioning
confidence: 90%
“…Their livelihood generally involves the gathering of jungle roots, wild fruit and vegetables, harvesting of forest products such as rattans or resins, fishing, hunting arboreal and burrow-digging animals, small-scale farming of crops and rubber, and the rearing of livestock to sustain their needs (Lye, 2011;Or & Tang, 2011). They have a profound traditional ecological knowledge about the forest, with a discerning understanding of plant-animal interactions (Ong, Campos-Arceiz, Loke, et al, 2021).…”
Section: Malayan Tapirs Tapirus Indicus and Gibbons Hylobates Agilis Andmentioning
confidence: 99%
See 3 more Smart Citations